Atomization Control to Improve Soft Actuation Through Vaporization - Lee, Han-Joo; Guerra-Bravo, Esteban; Baltazar, Arturo; Loh, Kenneth J. (Frontiers in Robotics and AI, 2021)
Soft actuation through droplet evaporation has significantly improved the actuation speed of methods that utilize liquid vaporization. Instead of boiling bulk liquid, this method implements atomization to disperse small droplets into a heater. Due to the large surface area of the droplets, the liquid evaporates much faster even at small temperature changes. However, further analysis is required to maximize the performance of this complex multi-physics method. This study was conducted to provide further insight into the atomizer and how it affects actuation. Numerical simulations were used to inspect the vibration modes and determine how frequency and voltage affect the atomization process. These results were used to experimentally control the atomizer, and the droplet growth on the heater surface was analyzed to study the evaporation process. A cuboid structure was inflated with the actuator to demonstrate its performance. The results show that simply maximizing the atomization rate creates large droplets on the surface of the heater, which slows down the vaporization process. Thus, an optimal atomization rate should be determined for ideal performance.